PENGARUH GOOD CORPORATE GOVERNANCE INDEKS DAN FINANCIAL DISTRESS TERHADAP NILAI PERUSAHAAN DENGAN KINERJA PERUSAHAAN SEBAGAI VARIABEL INTERVENING (STUDI PADA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BURSA EFEK INDONESIA (BEI) PERIODE 2009-2012) - Liza Tamarani; Yulia Efni; Haryetti - (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2015)
The purpose of this study was to determine whether there is any effect of good corporate governance index and Financial Distress to company value with corporate performance as an intervening variable in manufacturing companies listed on the Indonesia Stock Exchange 2009-2012.The population in this study was 143 Manufacturing companies listed on the BEI. The sample used in this study were 35 companies selected by purposive sampling. Hypothesis testing performed in this study by using statistical methods, namely; normality test, linear test, and coefficient of determination. Based on the hypothesis testing and data analysis has been conducted in this study can be concluded about the effect of corporate governance indices and Financial Distress on Company Value with the performance of the company as an intervening variable. Based on the results of this study indicate that the implementation of the GCG index has no significant effect directly to company performance. financial distress significantly influence directly to company performance, GCG index does not significantly influence directly to company value, financial distress does not significantly influence directly to the company value, the company performance has a significant effect directly to company value. This means that the company performance is only able to moderate the relationship between financial distress on the comapany value.Keywords: Good Corporate Governance index (GCG index), Financial Distress, Company Performance and Value Company